INFLUENCE OF THE EDUCATIONAL - EDUCATOR PROCESS ONACTUALIZATION OF ECOLOGICAL POTENTIAL OF FUTURE SPECIALISTS ON SOCIAL WORK - Palamarchuck, Olga (PSYCHOLOGICAL JOURNAL, 2017)
The article is devoted to the research of the influence of the educational process on actualization of the environmental potential of future specialists in social work. The meaning of the professional work of social work specialists in the context of transformational social change is to establish communication and explain innovation behavior from the standpoint of an environmentally-oriented way of life. The formation of a conceptual approach to the environmentally oriented activity of a social work specialist is based on the fact that modern activity is a peculiar form of human behavior, which is based on the actualization of the ecological potential; assuming responsibility for the consequences of the activity, readiness for making environmental decisions; the focus on the active transformation of the surrounding world. The developed program «Environmental formation of the future specialist in social work» is based on the creation of a reflexive environment, which would contribute to the awareness of the need for the formation of environmental professionalism among future specialists in social work and the implementation of appropriate motives of environmental and professional activities. This concept is based on the actualization of the environmental potential of future social work specialists, which will help them to master the main components of environmental professionalism; stimulating their desire to improve and implement ecological-professional abilities. It is shown that the most productive approach to the problem of actualization of the environmental potential of the personality of the future specialists in social work is systematic methodology with the leading position of unity of consciousness and activity. In this regard, the importance of the ecologically-innovative direction of professional activity, which involves the creation and implementation of various types of environmental innovations, which will cause changes in the activities of a specialist in social work in general, and in his person in particular. It is proved that updating of ecological potential is based on gradual advancement of future specialists in social work in understanding of own ecological responsibility and formation of ecological self-control in practical activity.